EFFECTIVE TEACHING METHODS IN THE MASTER’S DEGREE: LEARNING STRATEGIES, TEACHINGLEARNING PROCESSES, TEACHER TRAINING - Costa, Rebeca Soler; Laborda, José Luis Antoñanzas; García, Iciar Nadal (European Scientific Journal, ESJ, 2014)
The Bologna Process has substantially modified the structure of the new curricula at European universities, especially in the Masters degrees. Social and labour demands increasingly require more specialized professionals. The Faculty of Education at the University of Zaragoza implemented in the academic year 2009/2010 the Masters in Teacher Training for High School Teachersaimed at training future teachers of different degrees in the acquisition of teaching techniques and methodologies to carry out their professional work as teachers. This paper proposes objectives, methods and activities for achieving learning outcomes in the Masters compulsory module entitled "Context of Teaching Task" (CTT). The research developed has been carried out analysing students‘ training needs with the main aim of improving the teaching-learning processes in the Master´s Degree. It remains unquestioned the need to constantly updated the teacher training and provide them the necessary tools to be able to face new learning situations in their life-long learning process.